Postoperative dumping syndrome, health-related quality of life, anxiety, depression and eating disturbances: results of a longitudinal obesity surgery study - Astrid Müller; Salih Efeler; Nora M. Laskowski; Melanie Pommnitz; Julian W. Mall; Günther Meyer; Ruth Wunder; Hinrich Köhler; Thomas P. Hüttl; Martina de Zwaan (Obesity Facts, 2024)
Introduction: Given the lack of research on the relationship of post-surgery dumping syndrome and eating disturbances, the purpose of the present longitudinal study was to investigate whether dumping after obesity surgery is associated with pre-/postoperative eating disorder symptoms or addiction-like eating beyond the type of surgery, gender, HRQoL and anxiety/depressive symptoms. Methods: The study included 220 patients (76% women) before (t0) and six months after (t1) obesity surgery (sleeve gastrectomy n=152, Roux-en-Y gastric bypass n=53, Omega Loop gastric bypass n=15). The Sigstad Dumping Score was used to assess post-surgery dumping syndrome. Participants further answered the Eating Disorder Examination Questionnaire (EDE-Q), Yale Food Addiction Scale 2.0 (YFAS 2.0), Short-Form Health Survey (SF-12) and Hospital Anxiety and Depression Scale (HADS) at t0 and t1. Results: The point prevalence of symptoms suggestive of post-surgery dumping syndrome was 33%. Regression analyses indicate an association of dumping with surgical procedure (bypass), female gender, reduced HRQoL, anxiety/depressive symptoms and potentially with binge eating, but not with eating disorder symptoms in general or with addiction-like eating. Conclusion: The current study failed to show a close relationship between the presence of self-reported dumping syndrome and eating disorder symptoms or addiction-like eating following obesity surgery. Further studies with longer follow-up periods should make use of clinical interviews to assess psychosocial variables and of objective measures to diagnose dumping in addition to standardized self-ratings.